ADJAGENCY PAIR OF CONVERSATIONAL SCRIPT IN STORKS 2016 MOVIE - Silviani Nurfadilla; Siska Rizkiani (IKIP Siliwangi, 2021)
Communication is the process to share the information to other and understand the purposes between the speaker and hearer. This research contains a discussion identifying the adjacency pair as uttered by speaker which applied in Stork 2016 movie and to finding out the structures of Adjacency Pairs and analyze the conversations. An adjacency pairs is identified by different speakers between the second utterance as related to the first that composed of two turns produced which are placed adjacency. The study applied a descriptive-qualitative method. The conversation was analyzed by the type of adjacency pair (Sacks et al., 1974). It was found that in the movie there are greeting-greeting, question–answer, question–question, suggestion–acceptance, information–question, offer–refusal, question (inserted question - answer)–answer.Keywords: adjacency pairs, conversation analysis, utterance